Влияние крупных первичных интерметаллидов Al-Er на прочностные свойства сплавов Al-Mg - Кахидзе, Николай Иверьевич (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Increasing the strength properties of aluminum alloys is an urgent task of industry. The use of highstrength aluminum alloys containing scandium is limited by high cost. According to the action of reinforcing of aluminum alloys, erbium is similar to scandium, while the price of erbium is 32 times lower. This article investigates the effect of erbium on the structure, mechanical properties and the nature of the destruction of an alloy of the Al-Mg system in the cast state. The Al-Er master alloy for introduction into the melt was obtained by a promising hydrogenation method. A positive effect of erbium on the strength properties of aluminummagnesium alloy grade AA5056 is noted.